Cytotoxicity and genotoxicity of nano-silver in mammalian cell lines - Kim, Youn-Jung; Yang, Sung Ik; Ryu, Jae-Chun (Molecular & cellular toxicology, 2010)
Nano-silver (Ag) with antimicrobial activity is by far the most commercialized nano-compound. The hazards associated with human exposure to nanosized-silver should be investigated to facilitate the risk assessment process. Recent studies have shown that inflammatory, oxidative, genotoxic, and cytotoxic consequences are associated with silver particulate exposure, and are inherently linked. In the present study, the cytotoxicity and genotoxicity of nano-silver were investigated using the dye exclusion assay, the comet assay, and the mouse lymphoma thymidine kinase (tk +/− ) gene mutation assay (MLA). IC 20 values of nano-silver in L5178Y cells were determined the concentration of 3,769.53 μg/mL and 1,796.88 μg/mL with and without S-9, respectively. And in BEAS-2B cell, IC 20 values were calculated to 1,171.88 μg/mL and 761.72 μg/mL with and without S-9, respectively. From these results, nano-silver was more cytotoxic in absence of S-9 metabolic activation system and at the BEAS-2B cells. In the comet assay, L5178Y cells and BEAS-2B cells were treated with nano-silver which significantly increased >2-fold tail moment with and without S-9. However, the mutant frequencies in the nano-silver treated L5178Y cells were slightly increased but not significant compared to the vehicle controls with and without S-9. The results of this study indicate that nano-silver can cause primary DNA damage and cytotoxicity but not mutagenicity in cultured mammalian cells.